Boko Haram Terrorism and Socio-Economic Development in Borno State, Nigeria - Babajide, Jacob; Orji, Naomi (NIU Journal of Social Sciences; Vol 9 No 3 (2023): NIU Journal of Social Sciences, Vol. 9 No. 3, September 2023DO - 10.58709/niujss.v9i3.1710, 2023)
The violent extremist group, Boko Haram, operating in Northeast Nigeria has severely damaged the region's infrastructures and left thousands of people displaced. The incessant violent attacks had caused serious disruption and decline in economic activities, investment and education. This would have substantial implication for the socioeconomic development of the North-East generally, and Borno state particularly. Borno state is the epicenter of Boko Haram terrorism in Nigeria’s least developed geo-political zone. Terrorist activities over the years have further worsened the people’s already difficult socioeconomic conditions. Thus, the study adopted qualitative methodology to examine the effect of terrorism on Borno state’s socio-economic development. Hinged on state fragility theory, the study argued that whereas several efforts have been made to combat terrorism, Nigeria’s fragile and weak system greatly hampered these efforts. Considering the essentiality of education for long-term development, incessant abductions of pupils and disruptions of educational activities have further jeopardized the state's chances of development. The study found that terrorism has dealt a terrible blow on business activities, mobility, investment and educational opportunities in Borno state. In order to engender sustainable development, it is imperative that the Nigerian government, domestic stakeholders and international development partners intensify collaboration to address the menace of terrorism in Nigeria. Keywords: Boko-Haram, Displacement, fragility, Socio-economic development, Terrorism